Clinical evaluation of the effectiveness of interferential current therapy in the treatment of children with pelvic floor dyssynergia-type constipation: a randomized controlled study - Samhan, Ahmed Fathy; Abdelbasset, Walid Kamal; Elnaggar, Ragab Kamal (The Turkish Journal of Pediatrics, 2020)
Background. Despite several treatment modalities being described for pelvic floor dyssynergia-type constipation, the clinical evaluation of interferential current therapy (IFC) has not been examined. We aimed to examine the clinical effects of IFC therapy in the treatment of children with pelvic floor dyssynergia-type constipation. Methods. Between May 2018 and July 2019, this randomized controlled study included sixty-two children (46 boys and 16 girls) with pelvic floor dyssynergia-type constipation; their ages ranged between 7 and 15 years. The children were randomly divided into either the IFC group (n = 31) who received an active IFC therapy to stimulate the pelvic floor and external anal sphincter muscles, three times per week for four successive weeks, or the control group (n = 31) who received sham IFC stimulation. Stool-incontinence frequency per week, stool type, pelvic floor excursion, and myogenic activity of external anal sphincter were evaluated at the baseline, post-treatment, and three months after treatment termination. Results. The baseline evaluation showed non-significant differences between the IFC and control groups (p > 0.05). The post-treatment results showed a statistically significant difference between both groups regarding all variables, favoring the IFC group (p < 0.05). Further, the favorable effect of IFC on all variables continued at the follow-up, three months later. Conclusions. IFC therapy appears to improve stool-incontinence frequency, stool type, pelvic floor excursion, and myogenic activities of the external anal sphincter in children with pelvic floor dyssynergia-type constipation. These results suggest that adding IFC therapy to the medical treatment could improve the main features of pelvic floor dyssynergia-type constipation.